Selected Lectures of the 20th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 23-26, 2024 - - (Hygeia Press di Corridori Marinella, 2024)
Selected Lectures of the 20th International Workshop on Neonatology and Pediatrics; Cagliari (Italy); October 23rd-26th, 2024 CHILDREN'S HEALTH: MESSAGES FROM THE FUTURE   The Workshop has been organized with the patronage of Autonomous Region of Sardinia, City of Cagliari, Azienda Ospedaliera di Cagliari, University of Cagliari, Board of Physicians of the Province of Cagliari, Italian-Albanian Pediatric Society, AMBO (Alleanza per un Ambiente a misura di Bambino: alliance for a child-friendly environment), European Project Better4u, Eropean Project Life Milch, National Confederation of Pediatrics Heads (CONAPP), Italian Federation of Family Pediatricians (FIMP), Italian-Arabian Pediatric Society (IAPS), Italian-Romanian Pediatric Society (IRPS), Norman Group of Neonatal and Pediatric Nephrology, International Academy of Perinatal Medicine, Italian Society of Pediatric Allergology and Immunology (SIAIP), Italian Society of Clinical Biochemistry (SIBioC), Italian Society of Gynecology of Infancy and Adolescence (SIGIA), Italian Society of Neonatology (SIN), Italian Society of Hospital Pediatricians (SIPO), Association SIPO in the World, Italian Society of Pediatric Psichology (S.I.P.Ped.), Romanian Society of Pediatrics, Italian Society for Research on Essential Oils (SIROE), Italian Society of Neonatal Nursing (SIN INF), Union of European Neonatal and Perinatal Societies (UENPS).   LECT 1. NEONATOLOGY FROM THE PAST TO THE FUTURE • G. Buonocore (Siena, Italy) LECT 2. HUMAN BREAST MILK MICROBIOTA AND CHILDREN'S HEALTH • G. Corsello (Palermo, Italy) LECT 3. DEVELOPMENTAL NEUROBIOLOGY: THE EVOLUTION OF NEONATAL BRAIN • M. Ruggieri (Catania, Italy) LECT 4. FETAL PROGRAMMING OF ADULT DISEASES • G. Faa, M. Fraschini, F. Cau, V. Fanos (Cagliari, Italy; Philadelphia, PA, USA) LECT 5. SKIN MICROBIOTA IN ATOPIC DERMATITIS: IS IT POSSIBLE AN INTERVENTION? • D. Peroni (Pisa, Italy) LECT 6. SKINOMICS: SKIN METABOLOMICS AND MICROBIOMICS • A. Dessì, A. Bosco (Cagliari, Italy) LECT 7. PULMONARY HYPERTENSION IN THE NEWBORN • P.P. Bassareo (Dublin, Ireland ) LECT 8. LOOKING FOR A VEIN? THERE IS A LIGHT AT THE END OF THE TUNNEL • A. Lai, C. Lobina (Cagliari, Italy) LECT 9. NEONATAL TRANSPORT BY HELICOPTER • S. Rugolotto (Rovigo, Italy) LECT 10. THE NUTRIENT CYCLE: FROM MATERNAL NUTRITION TO HUMAN MILK COMPOSITION VIA PLACENTA-FETAL EXCHANGES • I. Ten-Doménech, A.C.C. Hodgson, P. Refinetti, J. Kuligowski, S. Rezzi (Valencia, Spain; Lausanne and Monthey, Switzerland) LECT 11. IS IT STILL TIME FOR SUSTAINED INFLATION IN THE DELIVERY ROOM? • G. Lista, F. Castoldi, F. Cavigioli (Milan, Italy) LECT 12. INFECTIONS AND ANTIMICROBIAL USE • A. Charitou (Athens, Greece) LECT 13. NEUROPROTECTIVE STRATEGIES FOR ASPHYXIATED NEWBORNS IN THE EARLY NEONATAL PERIOD: A FOCUS ON BRAIN-ORIENTED INTERVENTIONS • E. Gitto, F. D'Amico, A. Carcione, S. Calabrese (Messina, Italy) LECT 14. METABOLOMICS IN NECROTIZING ENTEROCOLITIS • A. Bosco, A. Dessì (Cagliari, Italy) LECT 15. LEVERAGING PREDICTIVE ANALYTICS FOR MATERNAL IMMUNIZATION • P. Jog, V. Joshi (Pune, Maharashtra, India) LECT 16. RESPIRATORY SYNCYTIAL VIRUS (RSV) PREVENTION: MESSAGES FROM THE PRESENT • L. Folgori, L. Barcellini, G.V. Zuccotti (Milan, Italy) LECT 17. GENETICS AND EPIGENETICS OF THE FUTURE • L. Stuppia (Chieti, Italy) LECT 18. MENINGITIS TODAY • G. Kuli-Lito, R. Petrela, B. Nezaj, B. Gjonaj, D. Shtembari, J. Zdrave, E. Hysenaj, R. Gjini, V. Mano, N. Gjylameti, E. Rustja, D. Cela (Tirana, Albania) LECT 19. BODY DYSMORPHIC DISORDER • F. Velardi (Rome, Italy) LECT 20. DECODING THE MIND: GENETIC INNOVATIONS IN PSYCHIATRIC RESEARCH AND TREATMENT • A. Ciubară (Galați, Romania)